The mediating effect of emotion regulation on the mindfulness and impulsivity of high school students - Lokita, Karisa Elisabeth; Siahaan, Frieda Maryam Mangunsong; Widyasari, Pratiwi (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Impulsivity increases the risk of addiction and negatively affects academic performance. One-way high school students can manage impulsivity is through mindfulness skills, in which the relationship between mindfulness and impulsivity can be mediated by emotion regulation. This study aims to establish whether emotion regulation plays a mediating role in the relationship between mindfulness and impulsivity in high school students. Quantitative research was conducted through mediation analysis using Hayes' PROCESS program. The Mindfulness Attention Awareness Scale (MAAS) was used to measure mindfulness; impulsivity was measured using the Barratt Impulsiveness Scale 11 (BIS-11); and emotional dysregulation using the Difficulties in Emotion Regulation Scale (DERS). The participants were 390 high school students in Indonesia aged 15-18. The results show that emotion regulation partially mediated the relationship between mindfulness and impulsivity (ab = -.11, SE = 0.02, 95% CI [-0.16, -0.07]). Mindfulness was found to improve emotion regulation skills and reduce impulsivity in high school students. The implications of the study are important in helping adolescents manage impulsivity, as they are at an age that is prone to risk taking. The use of mindfulness in schools could help manage emotional and behavioral problems in adolescents at high school age.